High resolution simulation of recent Arctic and Antarctic stratospheric chemical ozone loss compared to observations - Tripathi, Om Prakash; Godin-Beekmann, Sophie; Lefèvre, Franck; Marchand, Marion; Pazmino, Andrea; Hauchecorne, Alain; Goutail, Florence; Schlager, Hans; Volk, C. Michael; Johnson, B.; König-Lango, G.; Balestrie, Stefano; et al. (Journal of Atmospheric Chemistry, 2006)
Simulations of polar ozone losses were performed using the three-dimensional high-resolution (1° × 1°) chemical transport model MIMOSA-CHIM. Three Arctic winters 1999–2000, 2001–2002, 2002–2003 and three Antarctic winters 2001, 2002, and 2003 were considered for the study. The cumulative ozone loss in the Arctic winter 2002–2003 reached around 35% at 475K inside the vortex, as compared to more than 60% in 1999–2000. During 1999–2000, denitrification induces a maximum of about 23% extra ozone loss at 475K as compared to 17% in 2002–2003. Unlike these two colder Arctic winters, the 2001–2002 Arctic was warmer and did not experience much ozone loss. Sensitivity tests showed that the chosen resolution of 1° ×1° provides a better evaluation of ozone loss at the edge of the polar vortex in high solar zenith angle conditions. The simulation results for ozone, ClO, HNO 3 , N 2 O, and NO y for winters 1999–2000 and 2002–2003 were compared with measurements on board ER-2 and Geophysica aircraft respectively. Sensitivity tests showed that increasing heating rates calculated by the model by 50% and doubling the PSC (Polar Stratospheric Clouds) particle density (from 5 × 10 -3 to 10 -2 cm -3 ) refines the agreement with in situ ozone, N 2 O and NO y levels. In this configuration, simulated ClO levels are increased and are in better agreement with observations in January but are overestimated by about 20% in March. The use of the Burkholder et al. (1990) Cl 2 O 2 absorption cross-sections slightly increases further ClO levels especially in high solar zenith angle conditions. Comparisons of the modelled ozone values with ozonesonde measurement in the Antarctic winter 2003 and with Polar Ozone and Aerosol Measurement III (POAM III) measurements in the Antarctic winters 2001 and 2002, shows that the simulations underestimate the ozone loss rate at the end of the ozone destruction period. A slightly better agreement is obtained with the use of Burkholder et al. (1990) Cl 2 O 2 absorption cross-sections.